2002
DOI: 10.1002/path.1192
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of T cell receptor γ and immunoglobulin heavy chain gene rearrangements at the single‐cell level in lymphomas with dual genotype

Abstract: By prospectively studying immunoglobulin heavy chain gene (IgH) and T cell receptor gamma (TCRgamma) gene rearrangements in 398 lymphoma cases, a dual genotype was observed in 13% of B cell and 11% of T cell lymphomas. According to histological subtype, the highest incidence was observed for mantle cell lymphomas (32%) and lymphoplasmacytic lymphoma (21%) among B cell lymphomas, and for angioimmunoblastic lymphoma (AILT) (46%) and Sézary syndrome (SS) (50%) among T cell lymphomas. To determine whether the dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
(57 reference statements)
1
24
0
Order By: Relevance
“…Under these blinded conditions, we detected IGH clones in only 6 of 74 (8%) PTCL cases, consistent with previous reports on large series of PTCL (9 to 16%). [2][3][4][5][6] By contrast, we detected IGH clones in 23 of 24 (96%) pre-B-ALL cases, and similarly high rates of detection have been reported for pre-B-ALL. 18 -20 In regard to PTCL, the frequency of IGH clonality differed significantly from our previous report, in which we detected IGH clones in 33% of AILT cases and 35% of PTCL-U cases (P Ͻ 0.004).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Under these blinded conditions, we detected IGH clones in only 6 of 74 (8%) PTCL cases, consistent with previous reports on large series of PTCL (9 to 16%). [2][3][4][5][6] By contrast, we detected IGH clones in 23 of 24 (96%) pre-B-ALL cases, and similarly high rates of detection have been reported for pre-B-ALL. 18 -20 In regard to PTCL, the frequency of IGH clonality differed significantly from our previous report, in which we detected IGH clones in 33% of AILT cases and 35% of PTCL-U cases (P Ͻ 0.004).…”
Section: Discussionsupporting
confidence: 80%
“…Proof of lineage infidelity requires single cell analysis, which others have achieved by performing PCR on single cells isolated by microdissection. 6,24 However, the technical complexity of these experiments limits the number of cases that can be studied, and although evaluation for lineage infidelity is beyond the scope of this report, it remains a possible cause of IGH clonality. Several studies have shown that a single germinal center isolated by microdissection can yield an IGH clone by PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we considered that the muscle-infiltrated lymphocytes were clonal Tcells because a T-cell phenotype was shown by the immunohistochemical analysis. In addition, the frequency of dual genotypes of T-and B-cells in T-cell lymphomas was 11% in a previous study (4). Therefore, an additional diagnosis of Although combination chemotherapy with dexamethasone, etoposide, ifosfamide and carboplatin (DeVIC) normalized the serum CK levels, liver dysfunction and further elevation of the serum sIL-2R level were observed.…”
Section: ×10mentioning
confidence: 83%
“…In phenotypically equivocal cases, therefore, molecular investigation of immunoglobulin heavy chain (IgH)-and T-cell receptor gene rearrangements to establish the B-or T-cell histogenesis should also be considered, although cases with concurrent rearrangement of IgH-and T-cell receptor genes are reported with a frequency of approximately 10% for both B-and T-cell lymphomas, respectively. 21,22 Thus, lymphoma lineage determination should be based on a multimodal approach that considers morpho-, pheno-and genotypic characteristics.…”
mentioning
confidence: 99%